Harmony Amid Diversity: Multicultural Communication in the Youth Organizations of KNPI Gowa Regency - Zainuddin, Alumnuz (Institut Agama Islam Negeri Kerinci, 2023)
This research aims to understand the pattern of multicultural communication within a youth organization, namely the National Committee of Indonesian Youth (KNPI) in Gowa Regency. It is divided into two sub-problems: first, how the inter-agency relations become a pattern of multicultural communication within the youth organization KNPI Gowa Regency, and second, the consequences of multicultural communication for unity among youth organizations within KNPI Gowa Regency. This qualitative descriptive research employs a communication and phenomenology approach. Data sources are obtained directly from the Chairman, General Secretary, General Treasurer, and Youth Social Organizations (OKP) including Himpunan Mahasiswa Islam (HMI), Indonesian Islamic Student Movement (PMII), Indonesian National Student Movement (GMNI), Catholic Student Association of Indonesia (PMKRI), Catholic Youth, and Chinese Youth. Data collection methods include observation, interviews, documentation, and literature review. Data processing and analysis involve three stages: data reduction, data presentation, and drawing conclusions. The results of this research indicate that 1) Inter-agency relations form a multicultural communication pattern in the youth organization KNPI Gowa Regency, namely assimilation between communities (total communication pattern), collaborative (circular communication pattern), and dialogical communication pattern. 2) The consequences of multicultural communication for unity among youth organizations within KNPI Gowa include the creation of tolerance, meaning that the community or members of KNPI Gowa Regency always uphold an attitude of respecting and honoring differences. Additionally, the formation of solidarity among members, helping each other in different conditions to uphold togetherness.